Does acupressure therapy decrease blood pressure in hypertensive elderly? - Sang Ayu Ketut Candrawati; Ni Komang Sukra Andini (PROFESSIONAL HEALTH JOURNAL, 2025)
ntroduction: Hypertension is a high blood pressure condition often referred to as the "silent killer" as it is frequently asymptomatic but can lead to a range of serious health complications, including heart disease and stroke. The prevalence of hypertension continues to rise worldwide, with projections of reaching 29% of the adult population by 2025. To control hypertension, complementary therapies such as acupressure are emerging as a supportive complement to the management of high blood pressure, especially for the elderly, to improve their quality of life and ease the burden on the healthcare system. Objectives: to analyze the effect of acupressure therapy on blood pressure in hypertensive elderly. Methods: Pre-Experimental Design, with a One-Group Pretest-Posttest Design. Results: The results showed a decrease in average systolic blood pressure by 24.08 mmHg, from 148.08 mmHg in the pre-test to 124.00 mmHg in the post-test, with a p value of 0.002. In addition, there was a decrease in mean diastolic blood pressure by 11.83 mmHg, from 85.83 mmHg in the pre-test to 74.00 mmHg in the post-test, with a value of (p value 0.013). These results indicate that acupressure therapy has a significant effect on reducing systolic and diastolic blood pressure in elderly hypertension. Conclusions: These findings support using acupressure as a complementary therapy to assist in managing hypertension in the elderly, potentially improving their quality of life and reducing the burden of hypertension-related health services.